How substitutable are workers? Evidence from worker deaths - Simon Jäger; Jörg Heining (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
We estimate how exogenous worker exits affect firms' demand for incumbent workers and new hires. Drawing on administrative data from Germany, we analyze 34,000 unexpected worker deaths, which, on average, raise the remaining workers' wages and retention probabilities. The average effect masks substantial heterogeneity: Coworkers in the same occupation as the deceased see positive wage effects; coworkers in other occupations experience wage decreases when a high-skilled or specialized worker dies. Our findings imply substantial replacement costs, which are larger in thin markets and when skills are specialized. – – Wir schätzen, wie exogene Austritte von Arbeitnehmern die Nachfrage der Firmen nach etablierten Arbeitnehmern und Neueinstellungen beeinflussen. Basierend auf administrativen Daten aus Deutschland analysieren wir 34.000 unerwartete Todesfälle von Arbeitnehmern. Diese führen im Durchschnitt zu einer Erhöhung der Löhne und Verbleibwahrscheinlichkeiten der verbleibenden Arbeitnehmer. Hinter dem durchschnittlichen Effekt verbergen sich erhebliche Heterogenitäten: Mitarbeiter im gleichen Beruf wie der Verstorbene sehen positive Lohneffekte. Dagegen erfahren Kollegen in anderen Berufen Lohnkürzungen, wenn ein hochqualifizierter oder spezialisierter Arbeiter stirbt. Unsere Ergebnisse implizieren erhebliche Ersatzkosten, die in dünnen Märkten und bei spezalisierten Qualifikationen größer sind.
Keywords: J20; J30; J63; 330; Hiring Costs; Human Capital Specificity; Labor Market Thickness; Arbeitskräfte; Sterblichkeit; Personalbeschaffung; Personalmanagement; Humankapital; Arbeitsmarkt; Deutschland